Preliminary results on autochthonous populations of Lolium rigidum Gaud. from Aragon (Spain) - Delgado I.; Andrés C. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Variability and productivity of 13 autochthonous populations of Lolium rigidum Gaud. from Aragón were studied in order to use this species as a self-reseeding annual grass. Populations were compared to three foreign L. rigidum and four L. multiflorum Lam. cultivars during the 1995-96 period. The study was carried out under isolated plant and microplot conditions. Results proved the small variability between the autochthonous populations and their forage potentiality close to the control cultivars.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)